Co-localisation of insulin-like growth factor II and the proliferation marker MIB1 in hepatocellular carcinoma cells. Issue 2 (February 1997) - Sohda, T; Oka, Y; Iwata, K; Gunn, J; Kamimura, S; Shijo, H; Okumura, M; Yun, K
Abstract : AIM: To assess the effect of insulin-like growth factor II (IGF-II) on proliferation of hepatocellular carcinoma (HCC) cells. METHODS: Expression of IGF-II mRNA and protein was detected in 10 archival HCC specimens using in situ hybridisation and immunohistochemistry, respectively. Expression of the Ki-67 antigen, a proliferation marker, was determined immunohistochemically on the same sections. RESULTS: Increased expression of IGF-II mRNA and protein was detected in five of the 10 HCCs in cells located at the periphery of tumour nests. The pattern of localisation of IGF-II was almost identical with that of Ki-67 antigen. CONCLUSIONS: Most of the Ki-67 antigen positive cells co-expressed IGF-II, suggesting that IGF-II may act as an autocrine or paracrine growth factor, and may play an important role in the development of HCC.